2003
DOI: 10.1177/089484530302900401
|View full text |Cite
|
Sign up to set email alerts
|

Career Aspirations of Non-Managerial Women: Adjustment and Adaptation

Abstract: This study addresses career aspirations and planning among non-managerial women. Results indicate career goals often are adapted to meet other life circumstances ; and that family responsibilities, job security, and organizational support systems influence career success and satisfaction. Recommendations for organizationally based career initiatives focused on women in non-managerial positions are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 20 publications
3
48
0
6
Order By: Relevance
“…Women employed negotiation strategies and coping mechanisms to manage supports and barriers. The findings of this study are similar to those by Hite and McDonald (2003), Wentling (1996), and Hopkins and O'Neil, (2007).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Women employed negotiation strategies and coping mechanisms to manage supports and barriers. The findings of this study are similar to those by Hite and McDonald (2003), Wentling (1996), and Hopkins and O'Neil, (2007).…”
Section: Discussionsupporting
confidence: 81%
“…Many, however, admitted to reconsidering their career expectations and goals based on experiences in their personal and professional lives. This finding is supported by research by Hite and McDonald (2003), which found women adjust career aspirations and goals due to life circumstance.…”
Section: Coping Strategiessupporting
confidence: 75%
See 1 more Smart Citation
“…Adaptive goals, family influence, security needs, and support factors were the findings of a study conducted by Hite and McDonald (2003). Focus group interviews were conducted with 26 women to explore the non-managerial women's perspective of their career and the factors that facilitated and hindered their career plans.…”
Section: Discussionmentioning
confidence: 99%
“…Entre as investigações centradas em aspirações/objetivos, uma proposta de investigação que adquiriu espaço na literatura recente trata do construto Future Work Selves, definido como a representação do indivíduo sobre si mesmo no futuro com base em suas aspirações/esperanças em relação ao trabalho (Strauss, Griffin & Parker, 2012). Outra linha de pesquisa importante neste campo refere-se às aspirações e objetivos de carreira de mulheres em organizações, analisados principalmente a luz da busca pelo equilíbrio entre vida pessoal/familiar e o trabalho (Hite & McDonald, 2003;Walsh, 2012). No Brasil, a expressão projeto profissional, malgrado sua conotação flexível, costuma ser empregada em pesquisas sobre objetivos/aspirações de carreira.…”
Section: Futuro Na Carreira: Possibilidades De Investigação No Contexunclassified